2022
DOI: 10.21203/rs.3.rs-1478334/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of public health and infection control interventions during the severe acute respiratory syndrome coronavirus 2 pandemic on the in-hospital epidemiology of pathogens: In hospital versus community circulating pathogens

Abstract: Background: The first detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Germany was reported in early February 2020. In addition, extensive control measures on the coronavirus disease 2019 (COVID-19) pandemic have been placed in Germany since March 2020. These include contact and travel restrictions, distance rules, mandatory wearing of face masks and respirators, cancellation of mass events, closures of day-care centers, schools, restaurants and shops, isolation measures, and intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, frequent testing to identify infected individuals remains a cornerstone in curbing community transmission and has been modeled to be an effective intervention for countries transitioning toward endemicity (7). This is especially important in hospital settings where nosocomial SARS-CoV-2 and other infectious pathogens continue to pose a risk to vulnerable populations and healthcare workers (8)(9)(10). Therefore, an effective hospital surveillance programme, which allows rapid implementation of appropriate containment measures and re-allocation of healthcare resources is vital to mitigate preventable loss of life and the burden on the healthcare sector (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…However, frequent testing to identify infected individuals remains a cornerstone in curbing community transmission and has been modeled to be an effective intervention for countries transitioning toward endemicity (7). This is especially important in hospital settings where nosocomial SARS-CoV-2 and other infectious pathogens continue to pose a risk to vulnerable populations and healthcare workers (8)(9)(10). Therefore, an effective hospital surveillance programme, which allows rapid implementation of appropriate containment measures and re-allocation of healthcare resources is vital to mitigate preventable loss of life and the burden on the healthcare sector (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…An unexpected but positive phenomenon resulting from the mass implementation of these pandemic measures was the significant drop in non-COVID-19 respiratory viral infections and gastrointestinal viral infections globally. [4][5][6][7] An astounding decrease in influenza virus infections in both northern and southern hemispheres was by far one of the most noteworthy changes in non-COVID-19 disease incidence during the pandemic period. [8][9][10] Comprehensive analysis of the GISRS FluNet database in a 2022 study 10 showed that influenza cases sharply fell during the initial months of the pandemic to <100 cases per week.…”
mentioning
confidence: 99%
“…The near‐simultaneous global implementation of these nonpharmaceutical interventions helped to slow down the community transmission of SARS‐CoV‐2, mitigated the burden of disease on healthcare resources and allowed time to develop vaccines and treatments. An unexpected but positive phenomenon resulting from the mass implementation of these pandemic measures was the significant drop in non‐COVID‐19 respiratory viral infections and gastrointestinal viral infections globally 4–7 …”
mentioning
confidence: 99%